Islamic Dialectics and Culture in Establishing Islam Nusantara Paradigm: Variety Model of Islam Nusantara for Indonesia - Abdurrohman Kasdi (ADDIN, 2018)
This article examines the Islamic dialectics socio-culturallywhich inspires the establishment of Islam Nusantara. The method used in this research is qualitative with historical approach and included in the category of contemporary history. The step taken in this research is to reconstruct the tradition of IslamNusantara along with its cultural roots that lies behind it. The results show that: first, Islam has become the religion of most of the Indonesian people and has played many important roles in various social, political, economic, and cultural backgrounds. Secondly, Islam Nusantara is a typical Indonesian-Islamicstyle, which is a combination between Islamic theological teachings with the values of local traditions, cultures, and customs in this country. Third, the characters of Islam Nusantara show the existence of local wisdom in Indonesia that does not violate the teachings of Islam, instead they synergize the teachings of Islam with local customs scattered in Indonesia. Fourthly, Islam Nusantara is an Islamic practice in the country as a result of dialectics between shari'a text with local realities and culture. Therefore, Islam Nusantara comes not to change the doctrines of Islam, but to find ways how to embed Islamic values in the context of diverse cultural society.